Self-powered Through-wall communication for dry cask storage monitoring. (November 2022) - Sun, Kan; Wu, Yongjia; Qian, Feng; Jung, Hyunjun; Kaluvan, Suresh; Huijin, He; Zhang, Cheng; Reed, F. Kyle; Nance Ericson, M.; Zhang, Haifeng; Zuo, Lei
Highlights: A self-powered wireless through-wall communication system for nuclear waste storage. The thermoelectric generator could withstand 124 MRads and provide enough power. Sensing and communication electronics were implemented using JFETs under 2 Mrad. The through-wall ultrasound data transmission system survived 101 MRads. The integrated system could work appropriately under 195 ℃ before electronics died. Abstract: Many nuclear facilities, such as spent fuel storage dry casks and nuclear reactor pressure vessels, are entirely sealed by metal layers to prevent harmful radiation. For safety and security operations, the temperature, pressure, radiation, and humidity inside the vessel needs to be closely monitored. However, no practical technology is currently available to realize the through-wall data communication and monitoring for these vessels due to the inside harsh environment of high temperature and nuclear radiation. In this paper, an innovative self-powered wireless through-wall data communication system for the nuclear environment is presented, which demonstrates a successful solution to such challenges. The presented system is composed of four modules, i.e., energy harvester with power management circuits, ultrasound wireless communication using high-temperature piezoelectric transducers, electronic circuits for sensing and data transmission, and radiation shielding for electronics. Constitutive functions of each module were firstly designed and followed by the system integration. Experiments were conducted subsequently to validate the designed functions and evaluate the performance of the integrated system. Results showed that the average power of over 40 mW was harvested from the thermal flow inside the nuclear spent fuel canisters which could provide enough energy to operate the sensing and data communication systems. The gamma radiation test results showed that the thermoelectric energy harvester and ultrasound transceivers can withstand radiation dosing over 100 Mrad. Furthermore, temperature shock tests demonstrated that the entire system including the shielded electronics can survive and maintain their functionalities at temperatures as high as 195℃. Under the in-lab mocked-up high temperature conditions and radiation shielding, the proposed system is foreseen to survive and operate stably for fifty years inside a nuclear spent fuel canister, and send the frequency modulated data out of the canister for 3 s in every 10 min.